Effect of SiC Addition the on Adhesive Wear Resistance of 6061 T6 Aluminum Alloy - Hussain Ibrahem Al-Bayati, Siham (Anbar Journal of Engineering Sciences, 2012)
This paper is aimed to study the effect of SiC addition as reinforcement to 6061 T6 alloy. Al 6061 T6 alloy SiC composites were prepared by melting the alloy in a vortex and adding 4 % and 10% weight fractions of SiC. Then pouring the mixture into a mould to obtain a bar of 12 mm diameter and 150 mm length. Wear specimens were manufactured in dimensions of 20mm x 10mm according to ASTM to the base alloy and the cast matrix alloy. Microstructure have been carried out to understand the nature of structure and Hardness test also implemented to specimens. Adhesive wear test have been conduct both on the alloy and composites at different parameters (time, load and velocity). From the obtained results, it was found that wear resistance improved during the carbide addition comparing with the base alloy as a result of SiC addition which contributed in improving the hardness of the alloy that reflects to the wear resistance and these properties were improved as the increasing of the carbide silicon percentage.